NILAI PH DAN TOTAL ASAM LAKTAT SUSU PASTEURISASI DENGAN PENAMBAHAN EKSTRAK DAUN BINAHONG (Anredera cordifolia (Ten) Steenis) SELAMA PENYIMPANAN - Dwi Maryana; Suriani Suriani; Ali Akbar Wahab; Fatma Maruddin; Ratmawati Malaka (Jurnal Ilmu dan Teknologi Peternakan, 2022)
The utilization of Binahong leaf extract in pasteurized milk is an alternative to maintain the quality of pasteurized milk. The research objective was to determine the quality of pasteurized milk with the addition of binahong leaf extract and different storage times for pH values and lactic acid content. This study used a completely randomized design (CRD) factorial pattern with 2 (two) factors. The first factor (A) is the concentration of Binahong leaf extract (0%, 4%, 5%, 6%) and the second factor (B) is storage time (0 days, 3 days, 6 days, 9 days) of each the treatment, repeated 3 times. The results showed that the concentration of Binahong leaf extract, interaction time, and interaction had a very significant effect on the pH value of pasteurized milk. The effect of Binahong leaf extract and storage time had a significant effect on lactic acid content, but the interaction between the two treatments had no significant effect. The conclusion of this research is that the higher the concentration of Binahong leaf extract, the pH value decreases, and the lactic acid content of pasteurized milk increases. The longer the storage decreased the pH value,  but increased the lactic acid content of pasteurized milk. The concentration of Binahong leaf extract 0-6% and storage time of 6 days still has good pasteurized milk quality.